Esterification of the Carboxyl Groups in Fibrinogen by the Application of a Highly Specific Methylating Agent - Osbahr, A J (Thrombosis and Haemostasis, 1982)
The trimethyl oxonium ion specifically modified the free carboxyl groups of fibrinogen. This esterification process resulted in the polymerization of the modified fibrinogen molecule with the production of a polymeric material that resembled the physiologically formed fibrin clot. The extent of methylation of fibrinogen was evaluated by methoxyl determination at each step of the polymerization process. The modified fibrinogen polymerized in approximately ten min with a minimum number of methyl groups being incorporated into the fibrinogen molecule. In this manner, it was shown that modification of carboxyl groups in the fibrinogen by a group-specific methylating agent results in polymerization of the fibrinogen.The sites of methylation were ascertained by chromatographic analysis which resulted in the identification of β-methyl aspartic acid and γ-methyl glutamic acid derivatives of the fibrinogen. The analytical methods applied were not able to detect the methylation of any additional amino acid residues in the polymerized-methylated fibrinogen. Based on this experimental data, it was formulated that the methylation of fibrinogen involved the esterification of the carboxyl groups of aspartic and glutamic acid with the resultant reduction of negative repulsion between the fibrinogen molecules and thereby culminated in the polymerization of the modified fibrinogen.
Keywords: Fibrinogen; Trimethyl oxonium ion; Carboxyl groups; Polymerization; Methylation